Knowledge and attitudes about vitamin A consumption and its relationship with night blindness in university students - Suparmi, Suparmi; Prasetya, Harka; Rahmawati, Atik; Lailaulaan, Millam Shinta (Frontiers in Medicine, 2024)
Night blindness is the first sign of vitamin A deficiency (VAD), which can lead to blindness if left untreated. University students may be at risk of VAD-related night blindness due to unhealthy eating attitudes and inadequate vitamin A intake. This study aimed to determine the relationship between knowledge and attitudes toward vitamin A consumption affecting night blindness in university students. This cross-sectional study involved 409 third-year university students of Universitas Islam Sultan Agung, Semarang, Indonesia. Participants completed questionnaires about socio-demographics, their knowledge of vitamin A, and attitudes toward vitamin A consumption. Night blindness symptoms among university students were assessed using the Low Luminance Questionnaire (LLQ), followed by a bivariate analysis of the Chi-Square test. Multivariate binary logistic regressions were used to determine whether the independent variables were associated with night blindness. A p-value less than 0.05 indicated significance. The prevalence of high-symptom night blindness was higher among males (26.4%) than females (5.7%). Out of 409 university students, 48 from the non-medicine cluster of the study program had a night blindness symptom. The prevalence was lower in students who studied in the medicine cluster program. The level of knowledge on vitamin A had a significant relationship with symptoms of night blindness (prevalence ratio (PR) =2.239 (95% CI= 1.110-4.516). The attitudes towards vitamin A consumption were significantly associated with night blindness (PR = 2.560, 95% CI = 1.215-5.392). The results of this study show that the risk of night blindness in university students can be prevented by increasing their knowledge and attitudes toward consuming vitamin A-rich food. The university can provide health promotion and vitamin A supplementation to avoid night blindness among academia.